Hope Endures: Reading the Boston Marathon Bombing Through the Lens of Christian Hope - Heeder, Megan (Lumen et Vita, 2018)
Moral tradition teaches that there are particular clarifying events which aid the renewal of moral freedom, the pursuit of the good, and the promotion of justice. The Boston Marathon bombing is one of those events, inviting theologians to consider what a sacramentally-oriented systematic theology offers society via faith and culture’s engagement. Viewing the Boston Marathon bombings through Moltmann’s lens of Christian hope shows seeds of it in the community’s response: it was forward-looking and called people to action; it anticipated a justice connected to the reign of God; and it called people into communities of hope, like those of the disciples. Engaging the community’s response and individual stories from the bombing which embody these three aspects of Christian hope offer a sacramental vision of hope with the potential to give life to a largely secularized culture.